Selective-area growth of GaN microrods on strain-induced templates by hydride vapor phase epitaxy. (31st March 2016) - Lekhal, Kaddour; Bae, Si-Young; Lee, Ho-Jun; Mitsunari, Tadashi; Tamura, Akira; Deki, Manato; Honda, Yoshio; Amano, Hiroshi
Abstract: In this paper, we discuss the influence of parameters such as type of carrier gas and NH3 /HCl flow ratio on the growth of vertical GaN microstructures by selective-area growth (SAG) hydride vapor phase epitaxy (HVPE). On various strain-induced templates such as GaN/sapphire, GaN/Si, and AlN/Si, regular arrays of Ga-polar GaN microrods were properly achieved by adjusting the growth parameters. The photoluminescence and micro-Raman measurements reveal not only the crystal quality of the GaN microrods but also strain distribution. These results will give insight into the control of the morphology of GaN microrods in terms of the strain induced from templates in SAG-HVPE. The precisely controlled arrays of GaN microrods can be used for next-generation light-emitting diodes (LEDs) by realizing InGaN/GaN multi–quantum wells (MQWs) with a radial structure.